Impact of Extralegal and Community Factors on Police Officers’ Decision to Book Arrests for Minor Offenses - Crum, John D. (American journal of criminal justice, 2023)
Booked arrests carry greater harms than non-booked arrests. When booked following an arrest, individuals are confined without guilt and an official criminal record forms that carries several negative consequences. Even with these greater harms, police decision to book arrests is understudied with little research on what factors influence this decision. This study utilizes official booking data to determine if suspect extralegal and community factors affect officers’ decisions to book arrests across minor offenses. The study uses data from the Chandler Police Department in Arizona and the American Community Survey from 2013 to 2019. These data include suspect legal/extralegal, officer, time, and block-group level factors. Using a cross-classified modeling approach, we examine factors associated with booking arrests across five offenses (cannabis possession, drug paraphernalia, shoplifting, criminal damage, and non-DUI-traffic). Results suggest that legal factors, particularly felony charges, are associated with higher odds of booking after arrest. However, we also demonstrate how extralegal factors significantly impact police decision to book arrests. Native Americans, Blacks, older individuals, and those with prior records had higher odds of booked arrests. While the odds of booked arrest varied across officers and communities, few officer or community factors were related to the decision to book arrests. Results suggest extralegal factors remain significant across minor offenses. These findings highlight the need to examine disparities on police post-arrest outcomes, expand racial categories studied, and incorporate less utilized variables like prior record.